2017
DOI: 10.2147/bctt.s113025
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated radiation therapy for breast cancer: current perspectives

Abstract: BackgroundOwing to highly conformed dose distribution, intensity modulated radiation therapy (IMRT) has the potential to improve treatment results of radiotherapy (RT). Postoperative RT is a standard adjuvant treatment in conservative treatment of breast cancer (BC). The aim of this review is to analyze available evidence from randomized controlled trials (RCTs) on IMRT in BC, particularly in terms of reduction of side effects.MethodsA literature search of the bibliographic database PubMed, from January 1990 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…This technique of dose modulation has the potential to further decrease unwanted morbidity in patients treated with radiation therapy (RT) in certain disease sites while increasing RT dose homogeneity in the breast. 11 While Canadian and European trials of dose modulation showed decreased skin toxicity and improved cosmetic outcomes, dose modulation in those trials was considered to be more simple than dose modulation used in the United States. An NCDB analysis revealed increased use of IMRT from 5.3% in 2004 to 11.6% in 2009, and subsequent stabilization in 2011 at 10.7%.…”
Section: States Recent Analysis Of a National Cancer Database (Ncdb)mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique of dose modulation has the potential to further decrease unwanted morbidity in patients treated with radiation therapy (RT) in certain disease sites while increasing RT dose homogeneity in the breast. 11 While Canadian and European trials of dose modulation showed decreased skin toxicity and improved cosmetic outcomes, dose modulation in those trials was considered to be more simple than dose modulation used in the United States. An NCDB analysis revealed increased use of IMRT from 5.3% in 2004 to 11.6% in 2009, and subsequent stabilization in 2011 at 10.7%.…”
Section: States Recent Analysis Of a National Cancer Database (Ncdb)mentioning
confidence: 99%
“…Concurrent with the de‐escalation of radiation duration, more advanced radiation techniques known as intensity‐modulated radiation therapy (IMRT) have emerged. This technique of dose modulation has the potential to further decrease unwanted morbidity in patients treated with radiation therapy (RT) in certain disease sites while increasing RT dose homogeneity in the breast . While Canadian and European trials of dose modulation showed decreased skin toxicity and improved cosmetic outcomes, dose modulation in those trials was considered to be more simple than dose modulation used in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…With cumulative RT doses, serious late complications such as fibrosis, osteonecrosis, rib fracture and brachial plexopathy can occur more frequently [9,19]. Novel RT approaches such as intensity modulated radiation therapy and image-guided RT can minimize radiation exposure to uninvolved critical structures and enables less toxicity profile while increasing the applied dose [20]. Combination therapies with chemotherapeutics and targeted agents as radiosensitizers are another form of increasing therapeutic gain and proved benefit in many cancer sites as the standard treatment modality [21][22][23].…”
Section: Management Of Locoregional Recurrencementioning
confidence: 99%
“…Multiple studies have been done using techniques to improve the dosimetry of left sided breast radiotherapy. These include two main solutions: improving dosimetry through treatment planning [2,3] (IMRT, proton therapy etc.) or distancing the heart physically through technological advances [4,5] (Automated Breathing Control -ABC, Deep inspiration breath hold (DIBH)).…”
Section: Introductionmentioning
confidence: 99%